2017
DOI: 10.1097/md.0000000000009303
|View full text |Cite
|
Sign up to set email alerts
|

A study on dynamic monitoring, components, and risk factors of embolism during total knee arthroplasty

Abstract: Background:Fat embolism is a common complication of orthopedic surgery. However, the exact component and risk factor responsible for this complication remains unelucidated. This study aimed to detect the origin of the pulmonary embolus and identify relevant risk factors of pulmonary embolism in total knee replacement.Methods:A total of 40 osteoarthritis patients who underwent primary unilateral TKA were recruited into this study. Transesophageal echocardiography (TEE) was utilized to dynamically monitor the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In the present study the echogenic emboli detected on intraoperative TEE were seen in both RSA and THA groups at the time of reaming and artificial joint insertion. Lu et al demonstrated that in TKA the echogenic emboli observed on intraoperative TEE are taken up transvenously and consist of lipid droplets and bone marrow tissue [12]. Namely, they are thought to consist of lipid droplets and bone marrow tissue generated at the time of bone reaming and artificial joint insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study the echogenic emboli detected on intraoperative TEE were seen in both RSA and THA groups at the time of reaming and artificial joint insertion. Lu et al demonstrated that in TKA the echogenic emboli observed on intraoperative TEE are taken up transvenously and consist of lipid droplets and bone marrow tissue [12]. Namely, they are thought to consist of lipid droplets and bone marrow tissue generated at the time of bone reaming and artificial joint insertion.…”
Section: Discussionmentioning
confidence: 99%
“…In total hip arthroplasty (THA) and total knee arthroplasty (TKA), because the presence of echogenic emboli and snowstorm images identified intraoperatively by transoesophageal echocardiography (TEE) has been associated with the development of PE and DVT [9][10][11][12][13], intraoperative TEE is being increasingly used to clarify the developmental mechanisms of postoperative VTE. In contrast, because the incidence of PE and DVT in upper limb surgery is low and these cases are considered to be low risk, early ambulation and active movement may suffice as prophylactic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…HBL often occurs after joint replacement and traumatic fracture surgery, their common feature is that a large amount of fat droplets leak out of the medullary cavity, and penetrate deep into the circulation, tissues and cells; Especially during joint replacement, the manipulation of the femur and tibia can increase the pressure of the medullary cavity and force the fat particles into the blood circulation [6,7,22,23]. The effects of its metabolites on tissue cells need further study.…”
Section: Disscussionmentioning
confidence: 99%
“…The second operation is engaging a drill alignment guide to the tibial component and extending the tibial aperture by drilling a longitudinal channel through the tibia aperture and into the tibia. Both of these procedures will increase the pressure in the medullary cavity, where a large number of lipomicron may enter the circulation under high pressure [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is most commonly observed in cases of long bone fractures and during or following orthopaedic procedures such as total hip replacement (0.6%-10%) and total knee arthroplasty (TKA) (0.1%-12%) [[2], [3], [4]]. Risk factors include male sex, young adults, obesity, multiple fractures, and long bone fractures [5,6]. It is usually a diagnosis of exclusion and primarily based on clinical features using the Gurd and Wilson [7] criteria (Table 1).…”
Section: Introductionmentioning
confidence: 99%